MEMBRANE DISTILLATION FOULING CONTROL STRATEGIES ON XYLITOL CRYSTALIZATION - Grania Arsanti, Astrid
Xylitol is a sugar alcohol that can be used as a low calorie sweetener substitute for surcrose. Xylitol can be produced with biotechnology process by fermenting Oil Palm Empty Fruit Bunches (OPEFB) hydrolysate. The fermentation process produce impurities that need to be separated. Commercially, xylitol is available in the form of crystalline powder. Therefore a downstream process is required to conduct for the fermentation solution. The downstream process consist of pre-treatment for separation and purification, concentration, and crystallization of the solution. One of the most efficient and potential way to concentrate and crytallize the solution is by using membrane distillation, but there is a major obstacle in the use of it, named fouling. Fouling phenomenon can reduce xylitol production and reduce membrane lifespan. Therefore, the purpose of this study is to provide recommendations on strategies for preventing and controlling membrane distillation’s fouling in the xylitol crystallization process. In this study, the separation and purification process include centrifugation, activated carbon adsorption, filtration using UF membrane, and a variation consist of zeolite adsorption. The concentration and crystallization process are done by using MD. The feed will be made from fermented OPEFB hydrolysate. Mitigation experiments consist of aeration with flow variation (0,1; 0,15; 0,2 L/minutes) and air backwash with periodic time variation (30, 60, and 90 minutes). This study shows that the zeolite adsorption (after UF filtration) produce a clearer crystal and produce higher yield (34,08%) compared to UF permeate (31,68%), and needs shorter operation time. The main experiment of aeration and air backwash can reduce fouling, with air backwash once per 60 minutes as the best variation. The variation produce 34% yield and reach the saturated concentration by 8.5 hours.